Insect Consciousness - Overgaard, Morten (Frontiers in Behavioral Neuroscience, 2021)
The question of consciousness in other species, not least species very physically different from humans such as insects, is highly challenging for a number of reasons. One reason is that we do not have any available empirical method to answer the question. Another reason is that current theories of consciousness disagree about the relation between physical structure and consciousness, i.e. whether consciousness requires specific, say, neural structures or whether consciousness can be realized in different ways. This article sets out to analyze if and how there could be an empirical and/or a theoretical approach to the topic.